(untitled) (Journal of Informatics Education and Research, 2022)
Online discussion forums have become an increasingly popular tool for promoting student engagement in higher education. This paper explores the effectiveness of online discussion forums in promoting student engagement by reviewing and analyzing existing literature. The findings suggest that online discussion forums can effectively promote student engagement by fostering active learning, facilitating peer-to-peer interaction and collaboration, and promoting critical thinking and problem-solving skills. However, the success of online discussion forums in promoting student engagement depends on various factors, such as the quality of the forum design, the level of instructor involvement, and the level of student participation and motivation.